OVERVIEW OF AIRSPACE NOTAM SERVICES IN THE PIA UNIT IN THE MEDAN REGION IN THE SINGAPORE DELEGATION AREA - M Azanul Ashari; Elfi Amir; Rany Adiliawijaya Putriekapuja (Jurnal Teknologi Kedirgantaraan, 2025)
This study examines the effectiveness of the NOTAM service in Indonesian airspace delegated to Singapore, managed by the Medan Regional AIS Unit. Using a qualitative descriptive method with gap analysis, the research compares actual operations with ICAO and LOCA standards. Data were collected from July 2024 to August 2025 through observation, document review, and interviews. Analysis of three delayed NOTAM cases shows that while internal AIS procedures are generally compliant, effectiveness is hindered by delayed data submissions from external agencies. These delays violate ICAO Doc. 10066, limiting verification time, increasing operational stress, and posing flight safety risks. The study concludes that the core problem lies in the lack of compliance and awareness among external stakeholders. It recommends stronger dissemination of ICAO regulations, improved inter-agency coordination, and routine evaluations to ensure timely, accurate, and safe aeronautical information services.